The Paradoxes of Agrarian Reform in Russia. Book Review on Kalugina Z. The Paradoxes of Agrarian Reform in Russia: A Sociological Analysis of Transformation Processes. Novosibirsk: IEOPP SO RAN, 2000. - НикулинАлександр Михайлович (Journal of Economic Sociology, 2010)
Detailed description in the text